A Review on Hydroponics and the Technologies Associated for Medium- and Small-Scale Operations - Roberto S. Velazquez-Gonzalez; Adrian L. Garcia-Garcia; Elsa Ventura-Zapata; Jose Dolores Oscar Barceinas-Sanchez; Julio C. Sosa-Savedra (Agriculture, 2022)
According to the Food and Agriculture Organization of the United Nations, the world population will reach nine billion people in 2050, of which 75% will live in urban settlements. One of the biggest challenges will be meeting the demand for food, as farmland is being lost to climate change, water scarcity, soil pollution, among other factors. In this context, hydroponics, an agricultural method that dispenses with soil, provides a viable alternative to address this problem. Although hydroponics has proven its effectiveness on a large scale, there are still challenges in implementing this technique on a small scale, specifically in urban and suburban settings. Also, in rural communities, where the availability of suitable technologies is scarce. Paradigms such as the Internet of Things and Industry 4.0, promote Precision Agriculture on a small scale, allowing the control of variables such as pH, electrical conductivity, temperature, among others, resulting in higher production and resource savings.